Terra firma-forme dermatosis - a dirty dermatosis: report of two cases - Snehal Lunge; Supraja Chinthala (Our Dermatology Online, 2016)
Terra firma-forme dermatosis is characterized by 'dirty' brown-grey cutaneous patches and plaques that can simply be eradicated by forceful swabbing with alcohol pads. The pathogenesis has been attributed to abnormal and delayed keratinization. Although affected patients present with typical lesions, the disorder is not well-known by physicians. From a clinical point of view, we lay emphasis on its unique expression and diagnosis/treatment. From a histological perspective, we highlight its resemblance to dermatosis neglecta and speculate on the role of 'neglect' in a patient with seemingly adequate hygiene. The role of urea containing emollients in the development of this disorder remains to be determined.